Insects Associated with Cucumbers (Cucumis SativusL.) At Bamunka-Ndop(North West Region, Cameroon) - Esther Nadine Otiobo Atibita; Champlain Djieto-Lordon; Fernand-Nestor Tchuenguem Fohouo (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Studies on insects associated with cucumbers (Cucumis sativus) in Bamunka-ndop (North-West, Cameroon) under field conditions were conducted in 2017 and 2018 from April to July. The insect species diversity, the relative abundance, the frequency of visits and guilds were recorded on the plant from 7 am to 6 pm in a 2 hours time slots. Insects were found on the stem, leaves and flowers of Cucumber. There were 10 insect species belonging to 4 Orders. Out of these, four species belonged to Hymenoptera (54.15%), whereas the Coleoptera (33.18%), the Orthoptera (7.83%) and the Diptera (4.84%) owned two species each. Formica sp. being the most represented insect (24.42%) followed by A. mellifera (21.66%). Nectarivorous, pollinivorous, stems and leaves feeders and flowers and leaves feeders were found on the crop. The peak of activities of all the insect species was situated between 10 am and 12pm even though the temperature and the relative humidity of the study site appear not to affect their activities on the plant. These studies therefore indicated that the insects associated to cucumber should be exploited to work on their activities on cucumber and enhancing yield and quality of the fruits.